The enforcement of the European Account Preservation Order in the Portuguese legal system – A dematerialised procedure proposal - Lurdes Varregoso MESQUITA; Keriny BAIXO (Revista Jurídica Portucalense, 2022)
Obtaining a European Account Preservation Order (EAPO) under the procedure set out in Regulation 655/2014 of 15 May of the European Parliament and of the Council allows a judicial authority of a Member State (of origin) to order the preservation of bank accounts held by a debtor in another Member State (of destination). EAPO is a provisional, preventive and urgent instrument, with cross-border enforcement, which aims to provide security in economic and trade relations within the European area of justice. The enforcement of the EAPO, which is under the competence of the authority designated by each Member State – in the portuguese case, it is the Ordem dos Solicitadores e dos Agentes de Execução – follows internal law and must be speedy and effective. In Portugal, although an enforcement procedure is processed electronically, based on a dematerialised process, the enforcement of an EAPO does not follow a digital procedure, and this is criticised here, by proposing a model which would allow the development towards a dematerialised procedure that can be faster, safer and more efficient.